2004
DOI: 10.1523/jneurosci.0780-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and Degradative Sorting of NMDA Receptors by Conserved Membrane-Proximal Signals

Abstract: Regulation of the abundance of NMDA receptors (NMDARs) at excitatory synapses is critical during changes in synaptic efficacy underlying learning and memory as well as during synapse formation throughout neural development. However, the molecular signals that govern NMDAR delivery, maintenance, and internalization remain unclear. In this study, we identify a conserved family of membraneproximal endocytic signals, two within the NMDAR type 1 (NR1) subunit and one within the NR2A and NR2B subunits, necessary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 76 publications
4
102
0
1
Order By: Relevance
“…Calpain cleavage of the NR2B C terminus would be expected to accelerate receptor loss from the surface by unmasking an AP2 binding site that promotes NR2B endocytosis and trafficking to late endosomes for degradation (Scott et al, 2004). We hypothesized that loss of NMDARs from the surface of YAC128 MSNs would be enhanced as a result of calpain cleavage, and that this might explain the similar NMDAR current densities observed in YAC128 and WT MSNs while YAC72 MSNs exhibit enhanced NMDAR surface expression and current (Fan et al, 2007).…”
Section: Accelerated Loss Of Surface Nr2b Mediated By Calpain Activitmentioning
confidence: 99%
See 2 more Smart Citations
“…Calpain cleavage of the NR2B C terminus would be expected to accelerate receptor loss from the surface by unmasking an AP2 binding site that promotes NR2B endocytosis and trafficking to late endosomes for degradation (Scott et al, 2004). We hypothesized that loss of NMDARs from the surface of YAC128 MSNs would be enhanced as a result of calpain cleavage, and that this might explain the similar NMDAR current densities observed in YAC128 and WT MSNs while YAC72 MSNs exhibit enhanced NMDAR surface expression and current (Fan et al, 2007).…”
Section: Accelerated Loss Of Surface Nr2b Mediated By Calpain Activitmentioning
confidence: 99%
“…Increased levels of calpain-cleaved NR2B would be expected to enhance NMDAR endocytosis and lysosomal degradation (Scott et al, 2004). Although NR2B expression levels are similar for WT and YAC72 striatal tissue from 2-month-old mice , NR2B expression has not been assessed in brains from YAC128 mice.…”
Section: Nr2b Levels Are Decreased In Yac128 Striatummentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence also supports a role for exocytic and endocytic receptor cycling in controlling AMPAtype glutamate receptor abundance at synapses during synaptic plasticity, but NMDARs have conventionally been thought to be stably fixed within the postsynaptic density (PSD). Challenging this view, recent studies have revealed that NMDARs can move rapidly in and out of the neuronal surface [14][15][16][17][18][19][20] . Atleast some forms of NMDAR exocytic and endocytic trafficking require synaptic activity 21 or ligand binding 17,22 ,23 , and may initiate synaptic changes that lead to synapse stabilization or elimination during development 16,23 . Despite recent progress, our knowledge of how postsynaptic NMDARs are linked to and regulated by the endocytic machinery is only just emerging.…”
mentioning
confidence: 99%
“…The C0 domain contains two endocytic signals, tyrosine-based YKRH and lysine-based VWRK, which contribute to the endocytosis of NMDARs independent of NR2 subunits (Scott et al, 2004). The C0 domain also serves as a docking site for activated CaMKII (Leonard et al, 2002).…”
Section: Discussionmentioning
confidence: 99%